Validation Method on Green Analysis of Nitrite in Domestic Wastewater - Yuli Rohyami; Lutfiana Aida Rahmah; Endah Iniati (EKSAKTA: Journal of Sciences and Data Analysis, 2022)
The development and validation of methods on green analysis of nitrite in domestic wastewater has been carried out. This study is focused on the development and validation of nitrite determination using a smaller sample size with test kit nitrite from phosphoric acid, acid sulfanilamide, and N-(-naphthyl)-ethylenediamine dihydrochloride. The validation parameters studied include linearity, the limit of detection, the limit of quantification, precision, accuracy, and uncertainty. Based on the study, the green analysis procedure has good linearity with the linear regression equation of y = 2.8405x + 0.0043 with the correlation coefficient of 0.9992. Green analysis can be used detection and quantification nitrite in domestic wastewater at low concentration levels with the limit of detection of 0.01 mg/L and the limit of quantification of 0.03 mg/L. This green analysis procedure has good precision and accuracy with a % RSD of 1.61% and % recovery of 109.61%. Based on the study, the determination of nitrite with the green analysis method in domestic wastewater can be used at low concentration levels. The concentration of nitrite is 0.05 + 0.01 mg/L for inlet sample and 0.04 + 0.01 mg/L for outlet sample